Numerical investigation of a novel steel connection for panelized modular houses - Elhadary, Mostafa; Bediwy, Ahmed; Elshaer, Ahmed (Frontiers in Built Environment, 2026)
Indigenous communities in Canada, particularly those in remote areas, face a persistent shortage of adequate housing. Modular construction offers a potential solution, yet challenges related to transportation and lifting limit its widespread adoption. This study proposes an innovative steel bolted connection using hollow structural sections (HSS) to improve constructability and performance in modular housing. The connection was experimentally tested and validated using three-dimensional finite element models. A parametric study on one- and two-dimensional prototypes examined the influence of stiffeners, bolt arrangement, bolt number, and plate thickness on the connection’s structural performance. The results showed that the AR1.5 bolt arrangement increased capacity through early bolt bearing but reduced ultimate rotation by 50%, whereas the AR0.6 arrangement shifted failure to the column due to local buckling. Increasing plate thickness from 10 mm to 15 mm increased capacity by up to 7% and ductility by 11%, while increasing the number of bolts from six to ten improved capacity by up to 22%, depending on the arrangement. The addition of a 10-mm stiffener reduced ultimate rotation by approximately 60% due to local buckling. These findings highlight the critical role of bolt configuration and reinforcement techniques in optimizing both strength and deformation capacity, providing guidance for the design of efficient and durable modular housing connections.